Maya intellectual renaissance : identity, representation, and leadership - Montejo, Víctor, 1951- (Linda Schele series in Maya and pre-Columbian studies., 2005)
When Mayan leaders protested the celebration of the Quincentenary of the "discovery" of America and joined with other indigenous groups in the Americas to proclaim an alternate celebration of 500 years of resistance, they rose to national prominence in Guatemala. This was possible in part because of the cultural, political, economic, and religious revitalization that occurred in Mayan communities in the later half of the twentieth century. Another result of the revitalization was Mayan students' enrollment in graduate programs in order to reclaim the intellectual history of the brilliant Mayan past. Victor Montejo was one of those students. This is the first book to be published outside of Guatemala where a Mayan writer other than Rigoberta Menchu discusses the history and problems of the country. It collects essays Montejo has written over the past ten years that address three critical issues facing Mayan peoples today: identity, representation, and Mayan leadership. Montejo is deeply invested in furthering the discussion of the effectiveness of Mayan leadership because he believes that self-evaluation is necessary for the movement to advance. He also criticizes the racist treatment that Mayans experience, and advocates for the construction of a more pluralistic Guatemala that recognizes cultural diversity and abandons assimilation. This volume maps a new political alternative for the future of the movement that promotes inter-ethnic collaboration alongside a reverence for Mayan culture. -- Amazon.com